Evidence of nonlinear Walker circulation feedbacks on extreme El Nino Pacific diversity: Observations and CMIP5 models - Sulca, Juan (2021)
The work was performed using computational resources, that is, the HPC-Linux-Cluster, at the Laboratorio de Dinamica de Fluidos Geofisicos Computacionales (http://scah.igp.gob.pe/laboratorios/dfgc) at Instituto Geofisico del Peru (grants 101-2014-FONDECYT).